Removal of a femoral nail with osseous overgrowth at the end-cap: A navigated and cannulated minimally invasive technique. (January 2013) - Marintschev, Ivan; Rausch, Sascha; Fujak, Albert; Klos, Kajetan; Hofmann, Gunther O.; Gras, Florian
<x xml:space="preserve">Abstract</x> Intramedullary nail removal can be demanding, especially in cases of implant breakage or bony overgrowth at the end-cap, if the exact insertion depth of the nail is neglected in the index surgery. In the presented case, two challenging nail removals were necessary. The first was performed in a re-nailing procedure due to a pseudarthrosis with implant breakage, and the second was performed during hardware removal after fracture healing in a situation where there was deep intramedullary placement of the exchange nail. For the second implant removal a minimally invasive approach based on instrument placements over a navigated guide-wire was used to reduce the iatrogenic morbidity associated with an extensive open approach to the nail and to decrease the radiation exposure for the patient and the operating team.